MIKHAIL BULGAKOV AND HIS IMMORTAL NOVEL "THE MASTER AND MARGARITA" (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Mikhail Afanasyevich Bulgakov, a Russian writer and playwright, gave the world one of the most mysterious and multifaceted works of the 20th century - the novel “The Master and Margarita”.